The Analytical Methods Of Volterra Integral Equations of The Second Kind - Issa H. Al-Aidi; Ahmed Sh. Al-Atabi (Wasit Journal of Computer and Mathematics Science, 2023)
This paper discussed the analytic methods to solve Second order Volterra integral equations form using different methods. The domain decomposition method is the first technique. Depending on the hypothesis, the solution is by sequence. The second method is the successive approximation technique, which is used Picard iteration method. The third method used Laplace transformation. The modified decomposition technique is used as the fourth method. Depending on the Taylor series, the fifth method is called the series method. The last method solves the VIE using the functional correction technique called the variational iteration method. We introduce some examples to illustrate these methods.